2020
DOI: 10.1007/s13138-020-00178-9
|View full text |Cite
|
Sign up to set email alerts
|

Mathematische Modellierungskompetenz fördern durch Lösungsplan oder Dynamische Geometrie-Software? Empirische Ergebnisse aus dem LIMo-Projekt

Abstract: ZusammenfassungMathematisches Modellieren ist inzwischen ein fester Bestandteil des deutschen Mathematik-Unterrichts. Es existieren unterschiedliche Ansätze, wie der Aufbau dieser Kompetenz unterstützt werden kann. Der vorliegende Artikel stellt die Ergebnisse einer quantitativen Studie vor, bei der die Auswirkungen des Einsatzes zweier unterschiedlicher Hilfsmittel, zum einen eines strategischen Instruments, dem sogenannten Lösungsplan, und zum anderen einer dynamischen Geometrie-Software, auf den Aufbau von … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…This is also the case in the context of mathematical modelling (e.g., Greefrath et al, 2018;Keune & Henning, 2003;Sinclair & Jackiw, 2010). In this regard, some empirical results have already been reported (Hankeln & Greefrath, 2021). For example, in a case study, Greefrath and Siller (2017) observed students working on a reality-based task with GeoGebra.…”
Section: Connecting Educational Aspectsmentioning
confidence: 88%
“…This is also the case in the context of mathematical modelling (e.g., Greefrath et al, 2018;Keune & Henning, 2003;Sinclair & Jackiw, 2010). In this regard, some empirical results have already been reported (Hankeln & Greefrath, 2021). For example, in a case study, Greefrath and Siller (2017) observed students working on a reality-based task with GeoGebra.…”
Section: Connecting Educational Aspectsmentioning
confidence: 88%
“…Research on modelling has provided initial indications that reading comprehension prompts might foster the construction of a real-world model and thereby enhance modelling competence. In the study conducted by Schukajlow et al (2015) and similarly also in the study by Hankeln and Greefrath (2020), students received a scaffolding instrument called a solution plan to guide their modelling processes. The solution plan consisted of prompts referring to the different phases of the modelling cycle, including prompts to trigger reading comprehension ("Read the text precisely!…”
Section: Reading Comprehension and Its Impact On Constructing A Real-world Model And On Interest In Modellingmentioning
confidence: 99%
“…Furthermore, some studies addressed on how students effectively learn mathematics in online learning environments and the factors affecting their motivation positively or negatively (Bringula et al, 2021;Santi et al, 2022;Rutherford, et al, 2022). Although online learning environments have become so widespread, it is observed that recent research on mathematical modeling is mostly focused on face-to-face education environments (Hankeln and Greefrath (2021); Hıdıroğlu et al, 2018;Molina-Toro et al, 2022). Focusing on technology-aided mathematical modeling processes in face-to-face education, Çevikbaş et al, 2023 examined the difficulties that students face due to the complex nature of digital technologies and technology disruptions whereas Klock and Siller (2020) emphasized the limitations that students face in using technology and drew attention to the deficiencies in this regard.…”
Section: Introductionmentioning
confidence: 99%